Defending life: environmental crisis and Catholicism in Western Kenya - Sommerschuh, Julian (Religion, 2026)
Discussions of religion and ecology in Africa suggest a contrast between indigenous religions and Christianity. While indigenous religions are seen as environmentally friendly, Christianity is seen as promoting a harmful mindset of human dominance over nature. Drawing on ethnographic fieldwork with Kenyan Catholics, the article provides evidence to the contrary. I show that in a context of environmental crisis, the church in western Kenya offers ecological practices and ethics that promote human and other-than-human flourishing. I argue that the eco-friendly character of the Church here stems from a recognition of human dependence on the environment. Where ‘creation’ is destroyed, Western Kenyan Catholics observe, human beings suffer materially and spiritually. Their analysis motivates care for the environment, and demonstrates that Christianity can play a constructive role in addressing contemporary environmental challenges.